The effect of solvent on one-dimensional cadmium coordination polymers. (15th August 2018) - Notash, Behrouz; Rezaei Kheirkhah, Bahareh
Abstract : We transformed one one-dimensional coordination polymer directly to another by carrying out a dissolution–recrystallization structural transformation (DRST). Abstract : The assembly of 1, 4-bis(3-pyridyl)-2, 3-diaza-1, 3-butadiene (L ) with cadmium iodide in different solvent systems was investigated. The results showed the important role played by solvent, as two different one-dimensional coordination polymers were obtained depending on the solvent used. The use of MeOH, EtOH or MeCN as solvent yielded a 1D zigzag chain structural motif of [CdL I2 ] n (1 ). Our results showed solvent type to have a dramatic effect on the morphology and crystal habit of the resulting crystalline material of1 . Using DMSO as solvent yielded a 1D sinusoidal wave of [CdL I2 (DMSO)2 ] n (2 ). We also used dissolution–recrystallization structural transformation (DRST) with DMSO as the solvent to transform1 directly into2 .